(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The process of anticipating the stock market is one that is both difficult and time-consuming. On the other hand, advancements in stock market projection have begun to incorporate these methods of evaluating stock market data since the introduction of Machine Learning and its various algorithms. This has occurred since the beginning of the 21st century. We found that the Long Short Term Memory (LSTM) technique was the most effective when predicting stock values by using historical data. This was determined by analyzing the performance of the various algorithms in this endeavor. Because the algorithm has been taught using a massive accumulation of historical data and has been selected after being tested on a sample of data, it is going to be an excellent instrument for dealers and purchasers to utilize when they are investing in the stock market. According to the findings of this research, the machine learning model is superior to other machine learning models in terms of its ability to effectively predict market price.